2015
DOI: 10.2131/jts.40.437
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory reaction regulated by microglia plays a role in atrazine-induced dopaminergic neuron degeneration in the substantia nigra

Abstract: -Atrazine (ATR) is a widely used herbicide, although it is potentially ecotoxic. Increasing evidence indicates that ATR plays a critical role in inducing physiological changes to the endocrine and reproductive systems, and further may affect the nigrostriatal dopaminergic system in the diencephalon, resulting in altered dopamine (DA) levels in the striatum, transport and storage-related protein abnormalities in the synaptic terminals, motor function deficits, and degeneration of DA neurons in the substantia ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…See DOI: 10.1039/d1fo02857j Some studies have found that ATZ could induce inflammation in some tissues. [22][23][24] In addition, ATZ exposure can result in ROS generation and accumulation in its target organs. Thus, it could be hypothesized that ATZ induced the activation of Nlrp3, which could trigger autoinflammatory and metabolic disorders in human.…”
Section: Introductionmentioning
confidence: 99%
“…See DOI: 10.1039/d1fo02857j Some studies have found that ATZ could induce inflammation in some tissues. [22][23][24] In addition, ATZ exposure can result in ROS generation and accumulation in its target organs. Thus, it could be hypothesized that ATZ induced the activation of Nlrp3, which could trigger autoinflammatory and metabolic disorders in human.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Aroclor 1254 PCB mixture Mucio-Ramírez et al [ 41 ]: decrease somatodendritic vasopressin release Wei et al [ 42 ]: oxidative stress in the brain Coburn et al [ 43 ]: Inhibition of vasopressin release from magnocellular neuroendocrine cells Majumdar et al [ 44 ]: induces oxidative stress in the brain Tilson et al [ 45 ]: increases translocation of protein kinase C and decreases Ca2+-buffering in the brain 6 Arsenic (As) Heavy metal, pesticide Liu et al [ 46 ]: cognitive impairment Webb et al [ 47 ]: chronic neurological disease Preciados et al [ 48 ]: influence nuclear respiratory factor 1 by genomic and epigenomic networks, this contributes in the development of complex chronic human brain disorders Karri et al [ 49 ]: pro-oxidant elements dominate antioxidants factors and leads to cognitive dysfunction Tyler at al. [ 50 ]: alters epigenetics and hippocampal function, glutamatergic, cholinergic and monoaminergic signaling; altered adult neurogenesis; and increases Alzheimer's-associated pathologies 7 Atrazine Herbicide Ma et al [ 51 ]: reduces dopamine levels in the substantia nigra and corpus striatum in the midbrain Zhang et al [ 52 ]: severe dopamine neuron degeneration Lin et al [ 53 ]: increases in striatal dopamine; decreases in perirhinal cortex serotonin Ottinger et al [ 54 ]: impact on arginine vasotocin, catecholamines and gonadotropin releasing hormone. 8 Benzo(a)anthracene …”
Section: Resultsmentioning
confidence: 99%
“…5 c). The change of brain microenvironment and microglia activation induced dopaminergic neuronal injury [ 21 , 27 ]. We used TH antibody-labeled DA neurons via immunohistochemistry, where the siRNA injected via tail vein had no effects on DA neurons at the basal line.…”
Section: Resultsmentioning
confidence: 99%